Experience of health-system pharmacy administration residents in a longitudinal human resource management program. - Amerine, Lindsey B. (Poppe); Granko, Robert P.; Savage, Scott W.; Daniels, Rowell; Eckel, Stephen F. (American Journal of Health-System Pharmacy, 2014)
Purpose. The experience of health-system pharmacy administration (HSPA) residents in a longitudinal human resource (HR) management program is described. The subsequent benefits to the residents, department, and profession are also discussed. Summary. Postgraduate year 2 HSPA residents at an academic medical center desired more responsibility for managing an operational area. To this end, a program was created in which these residents directly manage a small group of pharmacy technicians and report to a clinical manager or assistant director with oversight responsibility. These “resident managers” are responsible, under the direction of the area’s clinical manager, for the personnel, schedule, time and attendance, and HR activities of the area. Resident managers have led and sustained operational improvement projects in their areas. In addition to providing learning experiences to residents, the HSPA residency program has also improved the operations of the areas in which these residents work. Benefits to the residents include conducting annual performance evaluations for employees with whom they have a relationship as it is a task every administrator completes. Resident managers at UNC have consistently stated that this longitudinal HR experience is one of the most rewarding and most challenging experiences offered in the two-year HSPA residency. The involvement of HSPA residents in longitudinal management responsibilities furthers residents’ leadership success by providing trained managers who are ready to immerse themselves into practice postresidency, having employee engagement and HR skills as well as experiences with leading operational improvements. Conclusion. A longitudinal HR management experience was successfully incorporated into an HSPA residency combined Master of Science degree program.